Impacts of Industry 4.0 in developed countries & BRICs - de Sousa, Guilherme Rodrigues [UNESP]; Muniz, Jorge [UNESP]; Valentim, Marta Lígia Pomim [UNESP]; Kipper, Liane Mahlmann; Mosconi, Elaine; Pereira, Márcio Giannini (FapUNIFESP (SciELO), 2025)
This paper aims to compare I4.0 manufacturing countries, providing an overview of the most relevant issues related to their patent and exportation figures. The countries researched are Germany, Brazil, China, South Korea, the US, India, Japan, and Russia. A Literature analysis was applied in Scopus and Web of Science publications (2012–2022), which include BRICs countries. Patent records related to high-tech products Patentscope of the World Intellectual Property Organization and the list of exported products in TradeMap were also searched to identify and analyze the contribution of each country’s policies. Findings present the positive effects of I4.0 policies in the industrial context of most countries, as evidenced by an increase in exportation and patents related to manufacturing high-tech goods since the policies were implemented after 2014. Patent registration evolution refers to the evolution of high-technology goods in the last nine years. This study also indicates the motivations of each country for implementing Industry 4.0. A country comparison of the durations, objectives, available funding, areas for action, focused manufacturing sectors, and prioritized technologies of these public policies supports researchers, managers, and policymakers.
Impactos da Indústria 4.0 em economias desenvolvidas e BRICs
Keywords: BRICs; Developed countries; Industry 4.0; Patents; Public policies